Implementasi Literasi Kesehatan Melalui Media Sosial untuk Siswa Sekolah Menengah Atas - Denniar Dedin; Anggita Faizah Ridwan; Ichsan Fauzi Rachman (Perpustakaan Universitas Riau, 2025)
This study aims to examine the implementation of mental health literacy through social media among senior high school students. A literature review method was employed to analyze various credible sources, including academic journals, articles, and research reports. The findings reveal that social media platforms such as Instagram, TikTok, and YouTube have significant potential as interactive and accessible educational tools to enhance students’ awareness and understanding of mental health. Social media also contributes to stigma reduction and provides a safe space for sharing experiences. However, several challenges arise, including low digital literacy, the spread of misinformation, cases of cyberbullying, and a lack of guidance from teachers and parents. Recommended implementation strategies include developing creative educational content, collaborating with digital influencers, and integrating mental health literacy into the school curriculum. The conclusion emphasizes the necessity of a collaborative and systematic approach involving schools, families, mental health communities, and social media platforms to optimize the digital ecosystem as a sustainable tool for supporting adolescent psychological well-being.